Super-selective prostatic arteries embolization in patients with benign prostate hyperplasia: prevention and treatment of complications - B. M. Shaparov; S. A. Kapranov; A. A. Kamalov; V. K. Karpov; A. G. Zlatovratskiy (Вестник урологии, 2021)
Introduction. Super-selective prostatic arteries embolization (PAE) is a modern minimally invasive surgical method for the treatment of benign prostatic hyperplasia (BPH). PAE is included in the Russian clinical guidelines for the BPH treatment and approved for use in the United States and European countries.Purpose of the study. To analyze the most common PAE-associated complications and to develop preventive arrangements.Materials and methods. During the period from 2013 to 2020, PAE as the main method of BPH treatment was used in 168 patients with an average age of 69.3 ± 8.1 (53-82) years. All patients underwent two-day antibiotic prophylaxis before the operation and lasted 7-10 days. For catheterization of the prostatic arteries, 2.0-2.8 Fr microcatheters and 4-5 Fr microconductors were used. For embolization, hydrogel microspheres with a diameter of 100-300 µm and 300-500 µm were used, as well as poly polyvinyl alcohol (PVA) microparticles with a diameter of 100-500 µm.Results. Bilateral PAE was successfully performed in 146 cases; unilateral PAE was performed in 22 patients due to anatomical features. Seventeen (10.1%) PAE from the orifice, super-selective PAE was performed in 67 (39.9%) cases, the PErFecTED embolization was performed in 84 (50.0%) patients. The most common complication was acute urinary retention (AUR) in 28 (16.6%) patients: trocar cystostomy was required in 11 (6.5%) patients, AUR was resolved using conservative therapy in 17 (10.2%) patients. In 23 (14.2%) cases, complications associated with unintentional embolization of the anastomoses of the prostate arteries were identified: rectal pain and/or the appearance of blood in the stool in 19 (11.3%) patients, the appearance of trophic ulcers on the glans penis in 5 (2.8%) patients. In addition, several adverse events that were not complications were noted: postembolization syndrome in 50 (29.7%) patients, and worsening of LUTS in 41 (24.4%) patients. Seven (4.1%) patients had acute epididymitis; 4 (2.4%) patients had a hematoma at the puncture site.Conclusion. PAE can cause a limited number of complications. It is necessary to unify the system for reporting PAE complications. Antibiotic prophylaxis is recommended. The use of visualization and X-ray navigation methods make it possible to make the PAE safer. The PErFecTED technique in combination with small particle sizes increases the risk of complications. The surgeon's experience and proficiency in special surgical techniques are essential. The transradial approach is promising, but further observation and an increase in patient samples are required. The question of choosing the optimal embolization drug continues to be relevant.